Glycosylation States of Pre- and Post-synaptic Markers of 5-HT Neurons Differ With Sex and 5-HTTLPR Genotype in Cortical Autopsy Samples - Nyarko, Jennifer N. K.; Quartey, Maa O.; Heistad, Ryan M.; Pennington, Paul R.; Poon, Lisa J.; Knudsen, Kaeli J.; Allonby, Odette; El Zawily, Amr M.; Freywald, Andrew; Rauw, Gail; Baker, Glen B.; Mousseau, Darrell D. (Frontiers in Neuroscience, 2018)
The serotonin (5-hydroxytryptamine, 5-HT) transporter (5-HTT) gene-linked polymorphic region (5-HTTLPR) is thought to alter 5-HT signaling and contribute to behavioral and cognitive phenotypes in depression as well as Alzheimer disease (AD). We explored how well the short (S) and long (L) alleles of the 5-HTTLPR align with serotoninergic indices in 60 autopsied cortical samples from early-onset AD/EOAD and late-onset AD/LOAD donors, and age- and sex-matched controls. Stratifying data by either diagnosis-by-genotype or by sex-by-genotype revealed that the donor's 5-HTTLPR genotype, i.e., L/L, S/L, or S/S, did not affect 5-HTT mRNA or protein expression. However, the glycosylation of 5-HTT was significantly higher in control female (vs. male) samples and tended to decrease in female EOAD/LOAD samples, but remained unaltered in male LOAD samples. Glycosylated forms of the vesicular monoamine transporter (VMAT2) were lower in both male and female AD samples, while a sex-by-genotype stratification revealed a loss of VMAT2 glycosylation specifically in females with an L/L genotype. VMAT2 and 5-HTT glycosylation were correlated in male samples and inversely correlated in female samples in both stratification models. The S/S genotype aligned with lower levels of 5-HT turnover in females (but not males) and with an increased glycosylation of the post-synaptic 5-HT2C receptor. Interestingly, the changes in presynaptic glycosylation were evident primarily in female carriers of the APOE ε4 risk factor for AD. Our data do not support an association between 5-HTTLPR genotype and 5-HTT expression, but they do reveal a non-canonical association of 5-HTTLPR genotype with sex-dependent glycosylation changes in pre- and post-synaptic markers of serotoninergic neurons. These patterns of change suggest adaptive responses in 5-HT signaling and could certainly be contributing to the female prevalence in risk for either depression or AD.